Akuntabilitas Pengelolaan Dana Desa dalam Akselerasi Pembangunan Desa di Desa Sukojati Kabupaten Banyuwangi - Shevilla, Eby Era; Shobaruddin , Muhammad; Hermawan, Hermawan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
Banyuwangi has received a Village Fund budget from the Central Government which will be distributed to all villages. To manage the funds that have been received, the Banyuwangi Regency Government has made an innovation, namely the E-Village Budgeting application. In managing the budget, the Village Government must also use the principles of managing regional finances, one of which is Accountability. Accountability is meant to carry out accountability for budget management activities to the community and also related parties. This study aims to describe the accountability of village fund management in accelerating village development in Sukojati Village. This study uses a qualitative approach. The method of data collection is by observation, documentation, and interviews in Sukojati Village. The research location is in Sukojati Village. The Sukojati Village Government has carried out accountability in the form of financial reports. However, the accountability carried out is still not good or in general is still minimal. This is because the Sukojati Village Government applies Accountability only when there is a problem in budget management.